Reduced aerosol transport from South Asia to the Tibetan Plateau following the January 2021 sudden stratospheric warming event - Yuling Hu; Haipeng Yu; Shichang Kang; Mian Xu; Siyu Chen; Junhua Yang; Xintong Chen; Jixiang Li (Communications Earth & Environment)
Abstract Aerosols from South Asia directly enhance glacier melt over the Tibetan Plateau. While the transboundary transport of aerosols from South Asia towards the Tibetan Plateau has been extensively investigated from a tropospheric perspective, less focus has been given to the stratospheric dimension. Here we examined the impact of the sudden stratospheric warming in January 2021 on aerosol transport from South Asia towards the Tibetan Plateau via numerical simulation. The results revealed that the aerosol transport from South Asia to the Tibetan Plateau reduced by 30%–40% following the January 2021 sudden stratospheric warming event. The eastward-propagating wave train stimulated by the stratospheric sudden warming induced an anticyclonic anomaly from the Persian Gulf to northern China, south of which easterly anomalies hindered the aerosol transport from South Asia to the Plateau. This study provides valuable insights for predicting air quality over the Tibetan Plateau.